The potential role of urban green areas for controlling ground surface and subsurface warming. Issue 1 (2nd January 2017) - Gunawardhana, Luminda Niroshana; Kazama, So
Abstract : Subsurface warming in urban areas is higher in magnitude than increases in surface air temperatures. However, little evidence exists on the effects of urbanization on subsurface environments, and there are few quantitative estimates of the effectiveness of adaptation measures. We analyzed the relationship between ground surface warming and the extent of landscape change using subsurface temperature anomalies as an indicator of surface warming in five urban areas in Japan. To interpret these results for urban planning, we presented the percentages of green areas that would be needed to achieve certain reductions in ground surface temperatures for areas with different urbanization levels. Accordingly, a 0.5 °C reduction in average ground surface temperatures can be achieved by an increased Normalized Difference Vegetation Index (NDVI) value of 0.035, which accounts for approximately a 17% increase in natural green areas in an area with 75% urbanization. This study provides quantitative estimates to cope with urban warming at the local scale in the face of climate change.